COMPETENCY-ORIENTED APPROACH IN THE ASSESSMENT SYSTEMS OF GERMANY AND UZBEKISTAN - Zuhra Najmiddinova; Abdullayeva Zarina Dilshodbekovna (TADQIQOTLAR, 2025)
The evolution of competency-oriented evaluation in the educational systems of Uzbekistan and Germany is covered in this article. The competency-based approach emphasizes  students'  capacity  for  independent  thought,  problem-solving,  and application of information in real-world contexts. Germany is renowned for its robust dual education system, which combines classroom instruction with job training. By implementing  criteria-based  evaluation,  bringing  national  standards  into  line  with international  frameworks,  and  enhancing  teacher  preparation,  Uzbekistan  is  now upgrading its assessment system. The two systems are contrasted in the article, along with their advantages, disadvantages, and potential future developments. Additionally, it  demonstrates  how  competency-oriented  assessment  helps  students  achieve  better learning outcomes and get ready for the demands of the modern workplace.